IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN BAHASA ARAB - nisak, Binti Khoirun (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
The government has set 2013 curriculum as learning curriculum to replace previous curriculum in order to improve education in Indonesia. This article is aimed to increase education quality in Arabic learning and to create qualified education in very aspect. This research shows that: 1) the implementation of scientific approach in Arabic learning in MAN Lab UIN Yogyakarta has run well based on the steps of scientific approach i.e. observing, questioning, gathering information or experiment, associating, and communicating. 2) the advantages of implementation of the scientific approach in Arabic learning are: learning activity can be implemented smoothly, the use of various learning media and adequate learning sources help student to learn actively. While the disadvantage of implementation is when this approach is implemented in a class that consists of students from various background inputs especially from SMP (Junior High School) students in which they do not have Arabic basis. So that if the learning centered on students, it can not be run well and the input result will be different.